A Paucisymptomatic Neuromuscular Disease Mimicking Type III 5q-SMA With Complex Rearrangements in the SMN Gene. (February 2014) - Lohkamp, Laura Nanna; Au, Katja von; Goebel, Hans-Hilmar; Kress, Wolfram; Grieben, Ulrike; Drossel, Karin; Garbes, Lutz; Wirth, Brunhilde; Heppner, Frank L.; Stenzel, Werner
Spinal muscular atrophy is an autosomal-recessive neuromuscular disorder, causing progressive proximal weakness and atrophy of the voluntary muscles. More than 96% of the spinal muscular atrophy patients show a homozygous absence of exons 7 and 8, or exon 7 only, in SMN1, the telomeric copy of the SMN gene. We report a young male patient with neurogenic symptoms and sparse muscle fiber atrophy, suggestive of a mild form of type III spinal muscular atrophy. He was found to be a carrier of intragenic mutations in both copies of the SMN gene, exhibiting a homozygous duplication of exons 7 and 8 in SMN1 and a homozygous deletion of exon 8 as well as a heterozygous deletion of exon 7 in SMN2 . However, an intact full-length SMN1 complementary deoxyribonucleic acid was identified, and SMN protein levels in a muscle specimen were identical to that of a healthy control, formally excluding the diagnosis of spinal muscular atrophy III.